An in-depth exploration of the post-test informational needs of BRCA1 and BRCA2 pathogenic variant carriers in Asia - Yuen, Jeanette (2021)
Identification of one's status as a BRCA1/2 pathogenic variant carrier often marks the start of navigating challenging decisions related to cancer risk management and result disclosure. Carriers report unmet informational needs, but studies have yet to explore the specific aspects of and how best to fulfill these needs. This study aims to explore the informational needs of BRCA1/2 pathogenic variant carriers in Asia to inform for the design of educational materials to support risk management decision-making.